2016
DOI: 10.4102/hsag.v21i0.1023
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cardiovascular risk factors and knowledge of cardiovascular disease in African men in the North-West Province

Abstract: Method: Questionnaires were completed by 118 African men from the North-West Province, South Africa, and health screening, including anthropometry, blood pressure, fasting blood sugar and cholesterol measurements, were done.Results: The mean CVD knowledge score was 75%. Participants' mean BP was 146/92 mmHg, falling within hypertensive ranges. Their mean fasting blood glucose of 5.8 ± 2.0 mmol/L exceeded the normal cut-off value of 5.6 mmol/L. There was a lack of association between CV risk factors and CVD kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
3
6
0
1
Order By: Relevance
“…With about four-fifths of participants having an overall adequate knowledge regarding CVD risk factors, this present study demonstrated a modest level of health literacy in an urban setting of SSA. Our rates of CVD literacy echoes findings of previous studies from South Africa [17], Iran [22] and Malaysia [23] which produced knowledge rates of 75.3, 78.7 and 81% respectively. Contrary to our findings, regional studies from Nigeria [24] (44%) and Cameroon [25] (47.5%) revealed considerably low rates of CVD literacy.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…With about four-fifths of participants having an overall adequate knowledge regarding CVD risk factors, this present study demonstrated a modest level of health literacy in an urban setting of SSA. Our rates of CVD literacy echoes findings of previous studies from South Africa [17], Iran [22] and Malaysia [23] which produced knowledge rates of 75.3, 78.7 and 81% respectively. Contrary to our findings, regional studies from Nigeria [24] (44%) and Cameroon [25] (47.5%) revealed considerably low rates of CVD literacy.…”
Section: Discussionsupporting
confidence: 88%
“…With regards to knowledge of specific risk behaviors, over nine-tenth of participants in this study recognized excess body weight, physical inactivity, and excess alcohol intake as risks, while more than threequarters acknowledged smoking, unhealthy diet, hypertension and diabetes as attributable risks. [17,[23][24][25][26][27][28][29][30][31] by 5.3-92.4%. Astonishingly, despite of a predominant blood-relationship between study participants and the escorted patients, just over one-third of participants realized they are living in a family with a positive CVD history and less than two-thirds were aware that it increases ones risk of CVD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these studies have focused on either the determination of CVD risk factors or the examination of CVD risk knowledge. Unfortunately, few studies have investigated the association between the risk status and knowledge regarding risk factors among individuals, some of which have reported a positive association (Balcı, Kolaç, Şahinkaya, Yılmaz, & Nirgiz, 2018; Lynch, Liu, Kiefe, & Greenland, 2006), some have reported a negative association (Flink, Sciacca, Bier, Rodriguez, & Giardina, 2013; Kilkenny et al, 2017), whereas others have reported no association (Burger, Pretrius, Fourie, & Schutte, 2016). However, only a few studies have examined the association between CVD risk status and CVD risk knowledge among individuals with diabetes (Angosta & Speck, 2014; Yılmaz, Kumsar, & Çelik, 2018).…”
Section: Introductionmentioning
confidence: 99%